Imaging guided percutaneous renal biopsy: do it or not? - Pagnini, Francesco; Cervi, Eleonora; Maestroni, Umberto; Agostini, Andrea; Borgheresi, Alessandra; Piacentino, Filippo; Angileri, Salvatore Alessio; Ierardi, Anna Maria; Floridi, Chiara; Carbone, Mattia; Ziglioli, Francesco; De Filippo, Massimo (Acta Biomedica Atenei Parmensis, 2020)
Since its first reported application, renal biopsy became an important part of the diagnostic algorithm, considered advantages and risks, to better manage therapeutic options. The biopsy can be performed with different techniques (open, laparoscopic, transjugular, transurethral and percutaneous). Currently, the percutaneous approach is the modality of choice. Percutaneous biopsy can be performed under CT or US guidance, but critical benefits and disadvantages have to be considered. Core needle biopsy is usually preferred to fine-needle aspiration because of the sample quality, usually obtaining multiple cores, especially in heterogeneous tumors. Principal complications are hematuria (1-10%), perinephric hematoma (10-90%), pneumothorax (0,6%), clinically significant pain (1,2%).